Energy, exergy, economic, environmental and sustainability (4ES) analyses of a wastewater source heat pump system for district heating applications based on real operational data. (March 2023) - Ozcan, Huseyin Gunhan; Hepbasli, Arif; Abusoglu, Aysegul; Anvari-Moghaddam, Amjad
Highlights: Wastewater source heat pump system for district heating is theoretically studied. EES model is developed based on real treatment wastewater data in winter months. Energy, exergy, economic, environmental and sustainability analyses are carried out. Five cities with distinct climatic characteristics in Turkey are considered. The proposed system is compared with the market leader heating system. Abstract: In recent years, worldwide interest in utilizing the heat energy from wastewater (WW) has increased significantly, concurrently with establishing policies and strategies for the sustainable management of WW. This study evaluated the 4ES performance of a photovoltaic-thermal powered WW source heat pump system for district heating applications with a series of Engineering Equation Solver (EES) simulations based on 20 different cases using actual data. The results indicated that the WW might have an energy rate potential of up to 25470 kW and an exergy rate potential of up to 2263 kW in January in a Koppen-Geiger-classified Dfb (warm-summer humid continental) climate. The highest and lowest exergy efficiency values ranged from 2.85 % to 98.24 % and from 74.80 % to 94.54 %, respectively for the employed components and the entire system. The environmental and sustainability studies utilized these simulated results to derive environmental effect factor (EEF) and exergy based-sustainability index (ExSI) values in the ranges of 0.58x10 -5 to 4.95x10 -5 and 3.97 to 18.32, respectively. In addition, the levelized cost of energy (LCOE) was modeled to be between 0.0801 ¢/kWh and 0.1341 ¢/kWh . In terms of sustainability, the proposed system demonstrated superior performance than the most common heating solution on the market (i.e. natural gas-fired heating system).